Paesaggi urbani e rurali in trasformazione contesti e dinamiche dell'insediamento letti alla luce della fonte archeologica : atti della giornata di studi dei dottorandi in archeologia (Pisa, 22 Novembre 2019), XXXIV ciclo di dottorato in scienze dell'antichita e archeologia consorzio delle Università di Firenze, Pisa e Siena - Fabiani, Fabio 1964-; Gattiglia, Gabriele (Archaeopress Publishing Ltd, 2021)
9 papers consider landscape transformations from a diachronic perspective. The volume addresses the landscape as a complex and dynamic entity characterised by a multiplicity of phenomena in continuous transformation produced by the interaction and mutual conditioning of natural and anthropic factors
Includes bibliographical references
Keywords: Archäometrie; Archäologie; Landschaft; Siedlungsarchäologie; Italien; Landscape archaeology / Congresses; Konferenzschrift -- 2019 -- Pisa